2015
DOI: 10.15259/pcacd.20.12
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic, Resorbable Dressing of Natural Polymers - Hemoguard

Abstract: Yellow 28 (BY 28) and acid Yellow 23 (AY 23) dyes onto chitin 34 M. Gierszewska-Drużyńska, J. Ostrowska-Czubenko Structural and swelling properties of hydrogel membranes based on chitosan crosslinced with glutaraldehyde and sodium tripolyphosphate 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The implants manufactured were tested for biocompatibility in accordance with the applicable ISO standards at the Department of Experimental Surgery and Biomaterials Research, Medical University in Wrocław, and at the National Institute of Health in Warsaw. Studies using experimental animals showed a weak cytotoxic effect, but not limiting the possibility of using the modified meshes in surgical procedures, and a lack of irritating or sensitising effects [62,63]. Researchers at Łukasiewicz-IBWCh have modified commercial cellulose products, commonly used in homes and hospitals, with nanoparticles of natural polymers in order to improve their physico-mechanical, sorption, and antimicrobial properties.…”
Section: Biomaterials Polymers In łUkasiewicz-ibwch Applicationsmentioning
confidence: 99%
“…The implants manufactured were tested for biocompatibility in accordance with the applicable ISO standards at the Department of Experimental Surgery and Biomaterials Research, Medical University in Wrocław, and at the National Institute of Health in Warsaw. Studies using experimental animals showed a weak cytotoxic effect, but not limiting the possibility of using the modified meshes in surgical procedures, and a lack of irritating or sensitising effects [62,63]. Researchers at Łukasiewicz-IBWCh have modified commercial cellulose products, commonly used in homes and hospitals, with nanoparticles of natural polymers in order to improve their physico-mechanical, sorption, and antimicrobial properties.…”
Section: Biomaterials Polymers In łUkasiewicz-ibwch Applicationsmentioning
confidence: 99%
“…They possess several unique properties including biodegradability, biocompatibility, low toxicity, low immunogenicity and antimicrobial activity . These biopolymers can be obtained from different sources such as microbial and animal and are used in various applications such as wound dressings, tissue scaffolds, cell encapsulation, drug delivery and also as cell delivery vehicles . Due to their simple processability, they can be fabricated in various forms such as gels, fibers, nano and microspheres and scaffolds .…”
Section: Introductionmentioning
confidence: 99%